Students’ Perspective toward English Learning for Non-EFL Students in Higher Education - Rahmad Risan (Journal of English Language Teaching, 2021)
English course should provide concrete evidence in supporting skills in various fields of science. This research aims to determine the extent of the material provided by lecturer of English courses in teaching non-EFL students. This research was descriptive qualitative research. Data was collected through questionnaires and interviews on research subjects. The subjects of this research were students at the Faculty of Sports Science, Universitas Negeri Makassar, consisting of 4 (Four) study programs: Sports Coaching Education, Physical Education. Recreation and Health, Elementary School Physical Education, and Sports Science. Researcher randomly selected ten (10) students from each study programs using purposive random sampling. Based on data from the results, twelve students (30%) thought that the most material needed in teaching English Material was Vocabulary. Ten (25%) students who thought that the most material needed was Speaking. Six (15%) students who thought that the most material needed was Listening. Five (12.5%) students who thought that the most material needed was Grammar.  Three (7.5%) students who thought that the most material needed was Writing.  Three (7.5%) students who thought that the most material needed was Reading. One (2.5%) student who thought that the most material needed was Pronunciation.